Analyzing Patient Medical Resume Coding’s Completeness and Accuracy on the Amount of INA-CBG’s Claims - Dorothy, Keithy; Kadir, Abdul; Rita, Kemala (International Journal Labs, 2022)
The figure for completing medical records of 100% has not yet been achieved which is the standard for completing hospital medical records after completion of service according to the Minister of Health of the Republic of Indonesia No. 129/MENKES/SK/II/2008, and the importance of diagnosis based on ICD-10 as one of the variables for calculating health service costs, this case study of breast cancer patients with operation was conducted to analyze the causes of that problem. The research object was to analyze the completeness and accuracy of the coding of medical resumes for breast cancer patients with surgery on the amount of INA-CBGs claims at Dharmais Cancer Hospital in 2019. This study research is a mix method, with qualitative and quantitative approaches. The qualitative approach was carried out by in-depth interviews, while the quantitative approach was carried out by reviewing the documents to be tested for suitability using the chi square method. The documents were inquired from Dharmais Cancer Hospital. The results showed the incompleteness fulfillment of medical resumes was highest. The secondary diagnosis of 30.23%, supporting examinations 27.91%, physical examinations and procedures/actions 23.26%, and identity of 4.65% of 43 cases were reviewed. Inaccuracy rate of primary diagnosis coding 90,7%, procedure 76,7%, secondary diagnosis 30,2%. Incomplete and inaccurate coding affects the final INA-CBG’s rate grouping results and is the cause of the difference in claims of Rp. 194,089,500.00 than it should be.